Effects of WTO accession on policy-making in sovereign states: Preliminary lessons from the recent experience of transition countries - Marc Bacchetta; Zdenek Drabek (World Trade Organization (WTO), 2002)
The purpose of the paper is to discuss the effects of WTO accession on policy-making and institutional reforms in transition countries. This is done by looking at the experience of those transition countries which are already Members of the WTO. We start by examining the effect of accession on trade policy and distinguish between the effects of accession negotiations and those of autonomous policy initiatives. Other areas of domestic policy-making considered in the analysis include market access, governance, government budget, structural reforms, trade and investment arrangements with regional partners and macroeconomic management. We find that no precise blueprint of accession conditions can be ascertained, that WTO played a role, albeit not an exclusive one in the process of liberalization, that the costs of WTO Membership are not negligible, that the benefits of WTO Membership are also significant in terms of a better market access, improved governance and a recourse to better economic policies.
Keywords: F1; F13; 330; WTO Accessions; Trade Policy; Transition Countries